ChemInform Abstract: Glycerol/Hypophosphorous Acid: An Efficient System Solvent‐Reducing Agent for the synthesis of 2‐Organylselanyl Pyridines. Issue 39 (5th September 2013) - Thurow, Samuel; Webber, Rodrigo; Perin, Gelson; Lenardao, Eder J.; Alves, Diego
Abstract The reagent system is employed for the in situ generation of organylselenols which react further with 2‐chloropyridines.